1987
DOI: 10.1136/thx.42.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Airway responsiveness in wheezy infants: evidence for functional beta adrenergic receptors.

Abstract: The effect of nebulised salbutamol on the bronchial response to nebulised histamine was studied in five wheezy infants aged 3-12 months. The response to doubling concentrations of up to 8 g/l of histamine was assessed by the change in maximum flow at FRC (VmaxFRc), measured by flow-volume curves produced during forced expiration with a pressure jacket. The concentration of histamine required to provoke a 30% fall in VmaxFRc (PC30) was measured. All of the infants responded to low concentrations of histamine du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 19 publications
0
22
0
2
Order By: Relevance
“…Double-blind placebo-controlled studies have demonstrated significant bronchodilatory effects [95][96][97][98] and protective effects against bronchoconstrictor agents [99,100] in infants and preschool children treated with rapidly acting inhaled b 2 -agonist. Thus, infants possess functional b 2 -receptors from birth, and stimulation of these receptors can produce the same effects as in older children, although paradoxical responses to inhaled b 2 -agonists have been reported in infants [50,101]. Oral administration of b 2 -agonist is also effective but is limited by systemic side-effects [102].…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Double-blind placebo-controlled studies have demonstrated significant bronchodilatory effects [95][96][97][98] and protective effects against bronchoconstrictor agents [99,100] in infants and preschool children treated with rapidly acting inhaled b 2 -agonist. Thus, infants possess functional b 2 -receptors from birth, and stimulation of these receptors can produce the same effects as in older children, although paradoxical responses to inhaled b 2 -agonists have been reported in infants [50,101]. Oral administration of b 2 -agonist is also effective but is limited by systemic side-effects [102].…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…The majority of infants we tested had a history of significant past wheezing illnesses, but none were symptomatic at the time of testing. Previous studies of bronchodilators in infants have evaluated: a) acutely wheezing infants 2,9,10,11 ; b) infants immediately prior to discharge following an admission with a wheezing illness 1 ; c) recurrently wheezy infants who were asymptomatic at the time of testing, 3,4,7 as in this study. We chose the latter of these three groups as the study population for this initial study since they had a small risk on administration of chloral hydrate compared to acutely wheezing infants.…”
Section: Discussionmentioning
confidence: 96%
“…Others have found no evidence of bronchodilator responsiveness using forced expiratory techniques in infants. 1,3 However, there is evidence that bronchodilators protect against induced bronchoconstriction 4 and also hasten its recovery. 5 There is debate as to what should be considered a significant response to bronchodilators; some suggest that it is more appropriate to take a fixed volume (of 180 ml in adults) rather than a percentage change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2002 Cochrane review sought to determine the effectiveness of b 2 -agonists for infants (,2 yrs) with ''recurrent or persistent wheeze'' [164]. Eight studies meeting the Cochrane criteria were identified [165][166][167][168][169][170][171][172]. Five studies had clinical end-points, and three assessed changes in lung function.…”
Section: Hypertonic Salinementioning
confidence: 99%